2016
DOI: 10.3168/jds.2015-9963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different scenarios for selective dry-cow therapy on udder health, antimicrobial usage, and economics

Abstract: The goal of dry-cow therapy (DCT) is to reduce the prevalence of intramammary infections (IMI) by eliminating existing IMI at drying off and preventing new IMI from occurring during the dry period. Due to public health concerns, however, preventive use of antimicrobials has become questionable. In this study, we evaluated the effects of 8 scenarios for selecting animals for DCT, taking into account variation in parity and cow-level somatic cell count (SCC) at drying off. The aim of this study was to evaluate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 33 publications
(53 reference statements)
2
68
1
5
Order By: Relevance
“…The standard practice has long been to treat all quarters from all cows (blanket approach) (Smith et al, 1967). Several countries have now opted for treatment only of quarters with previous risk for mastitis in the new lactation (e.g., high somatic cell count or positivity to culture) (Scherpenzeel et al, 2016). Concerns have been raised for the possible impact of the blanket approach on the selection of antibiotic resistance bacteria (Oliver and Murinda, 2012).…”
Section: Does Antibiotherapy Influence the Milk Microbiota Resistome?mentioning
confidence: 99%
“…The standard practice has long been to treat all quarters from all cows (blanket approach) (Smith et al, 1967). Several countries have now opted for treatment only of quarters with previous risk for mastitis in the new lactation (e.g., high somatic cell count or positivity to culture) (Scherpenzeel et al, 2016). Concerns have been raised for the possible impact of the blanket approach on the selection of antibiotic resistance bacteria (Oliver and Murinda, 2012).…”
Section: Does Antibiotherapy Influence the Milk Microbiota Resistome?mentioning
confidence: 99%
“…Individual SCC from a composite milk sample taken at the last milk recording before dry-off became the main selection criterion for the use of antimicrobials at dry-off (see Appendix for details). The SCC thresholds used in the guideline were based on the results of a deterministic modeling study by Scherpenzeel et al (2016a) and were expected to result in an optimal tradeoff between reduced use of antimicrobials associated with udder health (DCT and mastitis therapy) versus minimal increased risk of new IMI after the dry period.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recently, the European Commission Notice 299/04 recommended avoiding routine treatment of cows at dry-off (European Commission, 2015). The success of selective DCT and the effect on udder health depends on the accuracy [i.e., sensitivity and specificity of the selection procedure of the infected quarters/cows (Scherpenzeel et al, 2016)]. Identification of cows or quarters (or both) needing treatment at dry-off can be based on different criteria [e.g., individual cow SCC data and clinical mastitis history (Bradley et al, 2010;Rajala-Schultz et al, 2011), or on-farm milk culturing (Cameron et al, 2013)].…”
mentioning
confidence: 99%
“…Identification of cows or quarters (or both) needing treatment at dry-off can be based on different criteria [e.g., individual cow SCC data and clinical mastitis history (Bradley et al, 2010;Rajala-Schultz et al, 2011), or on-farm milk culturing (Cameron et al, 2013)]. In recent years, in some countries, such as in the Netherlands and Germany, selective DCT (Scherpenzeel et al, 2016) and use of ITS (Krömker et al, 2014) have been promoted as an alternative to blanket DCT. However, a recent study reported that in Germany, 79.6% of commercial farms used blanket DCT, and 64.9% of all antibiotic DCT were carried out without previous bacteriological examination (Bertulat et al, 2015).…”
mentioning
confidence: 99%